Intense plastic deformation of high-purity cast beryllium - Vasilev, A.A.; Stetsenko, S.P.; Vasilenko, R.L.; Malykhin, D.G.; Stoyev, P.I.; Khovrich, S.V.; Trembach, O.V.; Kovtun, K.V. (Вопросы атомной науки и техники, 2020)
The effect of intense plastic deformation on the mechanical properties, structure, and texture of high-purity cast beryllium was studied. For the first time, angular pressing of high-purity cast beryllium was carried out at temperatures of 600 and 500 °C. It is shown that the degree of grain refinement during angular pressing into a strip reaches a significant value. In one deformation cycle, the grain is crushed from 3 mm to 10 μm. The temperature dependences of the mechanical properties of the material of extruded billets in the initial state and after recrystallization annealing at a temperature of 650 °C for one hour were studied. It has been established that the best mechanical properties have samples of material deformed at 600 °C and subsequent annealing at 650 °C for an hour. Вивчено вплив інтенсивної пластичної деформації на механічні властивості, структуру і текстуру високочистого литого берилію. Вперше проведено кутове пресування високочистого литого берилію при температурах 600 і 500 0С. Показано, що ступінь подрібнення зерна при кутовому пресуванні в смугу досягає значної величини. За один цикл деформації зерно подрібнюється з 3 мм до 10 мкм. Вивчено температурні залежності механічних властивостей матеріалу видавлених заготовок у початковому стані і після рекристалізаційного відпалу при температурі 650 0С протягом однієї години. Встановлено, що кращі механічні властивості мають зразки матеріалу, деформованого при 6000С та після наступного відпалу при 650 0С протягом години. Изучено влияние интенсивной пластической деформации на механические свойства, структуру и текстуру высокочистого литого бериллия. Впервые проведено угловое прессование высокочистого литого бериллия при температурах 600 и 500 0С. Показано, что степень измельчения зерна при угловом прессовании в полосу достигает значительной величины. За один цикл деформации зерно измельчается с 3 мм до 10 мкм. Изучены температурные зависимости механических свойств материала выдавленных заготовок в исходном состоянии и после рекристаллизационного отжига при температуре 650 0С в течение одного часа. Установлено, что лучшие механические свойства имеют образцы материала, деформированного при 600 0С и после последующего отжига при 650 0С в течение часа.